2014
DOI: 10.1097/qad.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatitis C virus coinfection on CD4+ T cells of HIV-infected patients receiving HAART

Abstract: Whereas we could find no relationship between HCV infection and most indices of CD4⁺ T-cell homeostasis or activation, CD4⁺ RTEs are diminished in the circulation of HCV coinfected persons and appear to be related to indices of ongoing hepatic damage or inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
5
19
0
3
Order By: Relevance
“…Our study confirms several prior studies that found an association between HIV/HCV co-infection and a reduced immunologic, but not virologic, response to ART, [3][4][5][6][7][8][9] as well as studies demonstrating improved immunologic response among women compared with men. [20][21][22][23][24] Similar to the findings of a recent meta-analysis by Tsiara et al, 5 Int, p value for interaction across sex strata.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirms several prior studies that found an association between HIV/HCV co-infection and a reduced immunologic, but not virologic, response to ART, [3][4][5][6][7][8][9] as well as studies demonstrating improved immunologic response among women compared with men. [20][21][22][23][24] Similar to the findings of a recent meta-analysis by Tsiara et al, 5 Int, p value for interaction across sex strata.…”
Section: Discussionsupporting
confidence: 93%
“…1,2 HIV/ HCV co-infection may also reduce the response to antiretroviral therapy (ART), [3][4][5][6][7][8][9] and ultimately increase the risk of mortality among HIV-infected individuals. [10][11][12] HIV/ HCV-co-infected individuals are considered a priority population for HCV treatment due to more rapid liver disease progression in the setting of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported increased apoptosis in total [58, 103, 104] and in T CM [58, 105] CD4 T cells from patients with HIV, which is an explanation of CD4 T cell loss in chronic infection [106]. These and other studies [13, 5760] inferred apoptosis by demonstrating Annexin V binding to viable cells; however, it has been demonstrated that Annexin V binding can be increased in other cell death pathways [107110]. In this regard, we found that HIV infection altered the expression of a considerable number of genes that indicated that apoptosis would not be favored.…”
Section: Discussionmentioning
confidence: 68%
“…Since the predictions of increased proliferation and increased cytostasis were incompatible, and the prediction of reduced apoptosis did not agree with previous evidence [13, 5760], we took into account that enrichment tools base their predictions on a broad set of previous findings, ranging from very particular to very general ones. Accordingly, we investigated if the predictions were based on more demarcated processes, and if these processes were compatible.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study the levels of activated CD8 + T cells, evaluated as the simultaneous expression of HLA-DR and CD38, were similar in coinfected and monoinfected subjects, with significant differences found only in the CD4 + T cell subset. 24 Indeed, these higher levels of HLA-DR + CD38 + CD4 + T cells among coinfected patients were closely correlated with lower CD4 + T cell counts and, thus, with the CD4:CD8 ratio. Moreover, the correlation between the levels of HLA-DR +-CD38 + CD8 + T cells and sCD14 suggests a link between innate and adaptive immune activation among HIV/HCV-coinfected individuals.…”
Section: Discussionmentioning
confidence: 97%